Measuring advertising's effect on mental availability. (September 2021) - Vaughan, Kelly; Corsi, Armando Maria; Beal, Virginia; Sharp, Byron
This study shows that the impact of advertising on consumer memory can be observed using mental availability (MA) metrics. Four MA metrics are used to measure the effect of advertising on a brand's mental availability, with the results showing that in the majority of cases, MA metrics are greater among both brand users and non-users who are aware of the brand's advertising, with a greater effect among non-users. From a practical market research perspective, adding MA metrics to existing brand health tracking will have no data collection costs where brand perceptions are already being measured.